Bilateral femoral hernias in a male child as the initial presentation of Ehlers-Danlos syndrome - Melissa Wong; Patrick J. Javid (Elsevier, 2020)
In this article, we present an unusual case of a young boy who presented with bilateral groin hernias. Surgical exploration ruled out inguinal or direct hernia and subsequent workup including a repeat ultrasound revealed bilateral femoral hernias. Given the patients previous history of joint hypermobility and the rarity of bilateral femoral hernias, the patient was subsequently evaluated for a connective tissue disorder and was ultimately diagnosed with Ehlers-Danlos syndrome (EDS). There are no other such reported cases in the literature. This case highlights the potential association between connective tissue disorders and bilateral femoral hernias in young children.